Sosialisasi Kampanye PROKES (Program Kembali Ke Sekolah): Pembelajaran Tatap Muka (PTM) Terbatas pada Pandemi Covid-19 di SMP Bina Taruna Bandung - Rahmiati Aulia; Aisyi Syafikarani; Olivine Alifaprilina Supriadi; Siti Hajar Komariah; Rully Sumarlin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Program services for SMP Bina Taruna Bojongsoang, Bandung, which is routinely held, problems were formulated regarding procedures and health protocol facilities that were not adequate when implemented (Face-to-Face Learning). The results of these observations are the background for the design and socialization of the PROKES (Back to School Program) campaign for SMP Bina Taruna Bandung. This activity is expected to support the limited PTM (Face-to-Face Learning) process to build awareness of school residents while maintaining orderly health protocols to prevent the spread of COVID-19. The PROKES campaign socialization activity (Back to School Program) was carried out by designing campaign attributes and applications at SMP Bina Taruna Bandung. The evaluation of this campaign's socialization received positive responses following the lack of facilities and facilities for the need for orderly health protocols in the implementation of PTM. Participants who are teachers, staff, and students of SMP Bina Taruna are greatly helped by this activity.